The role of BCG in prevention of tuberculosis and the strategies to improve its immunogenicity - Mazurek, Jolanta (Health Promotion & Physical Activity, 2018)
Tuberculosis (TB) remains a major public health problem and the main cause of death from the infectious diseases worldwide. Mycobacterium tuberculosis (Mtb), a causative agent of tuberculosis, is the oldest known human pathogen. The only available TB vaccine, BCG, was first administered in 1921 and since then remains the only protecting tool against TB. Yet, its efficacy is limited and there is an urgent need to design and produce a novel vaccine that will protect against this deadly disease in the era of emerging problems with antibiotic resistance. In this review a current, global TB situation is outlined and the characteristics of BCG are presented. Finally, the strategies leading to generation of BCG variants providing improved protecting efficacy are shortly described.